All Days 2011
DOI: 10.2118/147863-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Enzyme Breaker for Mudcake Removal in High Temperature Horizontal and Multi-lateral Wells

Abstract: Effective removal of drilling-mud filter cake during well completion is essential to reduce the formation damage caused by drilling activities in many production and injection wells. This task is very difficult to achieve, especially in horizontal/multilateral wells. Harsh chemical treatments (acids, oxidizers, and chelating agents) have been used extensively to conduct water-based mudcake cleanup treatments. However, these approaches have been limited due to the associated high corrosion rates and un-even mud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(16 reference statements)
2
6
0
Order By: Relevance
“…These results are consistent with earlier results of Ghosh et al, 30 who reported that the clean-up efficiency of their investigated solution comprising 3% acetic acid and hydrolase enzyme was above 90%. Similar results are also reported by Al-Khaldi et al, 37 through coreflood studies.…”
Section: Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with earlier results of Ghosh et al, 30 who reported that the clean-up efficiency of their investigated solution comprising 3% acetic acid and hydrolase enzyme was above 90%. Similar results are also reported by Al-Khaldi et al, 37 through coreflood studies.…”
Section: Results and Discussionsupporting
confidence: 91%
“…This is consistent with the recommended limit of acid in the clean-up fluid as suggested by previous authors. 30 , 37 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They catalyze the hydrolysis reaction of the β-1,4 glycosidic bond between the mannose molecules in the polysaccharide backbone to produce simple sugars such as monosaccharides or disaccharides that are soluble in water. Some examples of enzymes used in the oilfield include Amylase, Cellulase, Hemicellulase, Pectinase, and Mannanase [ 57 ].…”
Section: Introductionmentioning
confidence: 99%